PERANAN KOPERASI SEKOLAH TERHADAP PENINGKATAN SOFT SKILL PESERTA DIDIK DI SMK NEGERI 1 PONTIANAK - Cantisa, Maria Ursula; Herkulana, Herkulana; Khosmas, F. Y. (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractBased on the research entitled " Increasing students soft skill towards the role of school cooperatives in SMK Negeri 1 Pontianak", the research problem of this research by using formulation "What is the role of the school cooperatives in increasing soft skills to the students accounting majors in SMK Negeri 1 Pontianak?". The population was 90 students and the sample was 47 students. The researcher applied quantitative research approach, with the data collection  used questionnaire. The data processing used SPSS version 18.00. The test of validity applied 8 instruments were declared valid, and 22 instruments were invalid. The reliability test stated that all instruments exceeding 0.6 were declared feasible. Normality of data used the Kolmogrov-Smirnov test, data was normally distributed with a significance value of 0.982 with the value above, the probability was 0.05. The results showed that the school cooperatives have a role in increasing the soft skills of students in SMK Negeri 1 Pontianak. This was indicated by based on the calculation of r_ (count) of 4,615, indicated that there was a role for the independent variable (X) against the dependent variable (Y). When compared with r_ (table) (n = 47) of 1.678, then r_ (count)> r_ (table), i.e. (4.615> 1.678), so Ha was accepted. The role of school cooperatives in increasing the soft skills of students in SMK Negeri 1 Pontianak by 32.1%, the correlation coefficient of 0.567 from the summary model table, this figure is between 0.40 - 0.599, which is the medium category.Keywords: Role, School Cooperatives, Soft Skills, and Students